2016
DOI: 10.1080/08897077.2015.1135225
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Methadone Maintenance Treatment Patients Prescribed Opioid Analgesics

Abstract: Background Opioid analgesic use and disorders have dramatically increased among the general American population and those receiving methadone maintenance treatment (MMT). Most research among MMT patients focuses on opioid analgesics misuse or disorders; few studies focus on MMT patients prescribed opioid analgesics. We describe demographic, clinical, and substance use characteristics of MMT patients prescribed opioid analgesics and compare them to MMT patients not prescribed opioid analgesics. Methods We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The prevalence of AOP was lower in the CNCP OST patients compared to CNCP control patients (47.8 vs. 68.0%). We observed similar prevalence of AOP in CNCP OST patients as that reported in prior studies, where prevalence ranged between 43 and 47% ( 17 , 21 , 27 ). Furthermore, following adjustment for age, gender, low-income status, mental health disorder, HCV infection, and alcohol use disorder, our findings revealed a 2.7-fold decrease in the prevalence of AOP in CNCP OST patients compared to CNCP control patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of AOP was lower in the CNCP OST patients compared to CNCP control patients (47.8 vs. 68.0%). We observed similar prevalence of AOP in CNCP OST patients as that reported in prior studies, where prevalence ranged between 43 and 47% ( 17 , 21 , 27 ). Furthermore, following adjustment for age, gender, low-income status, mental health disorder, HCV infection, and alcohol use disorder, our findings revealed a 2.7-fold decrease in the prevalence of AOP in CNCP OST patients compared to CNCP control patients.…”
Section: Discussionsupporting
confidence: 89%
“…Thirdly, there is wide abuse in terms of diversion associated with analgesic opioids in OST patients, where pain may be reported solely to manipulate prescribers to obtain opioid medication. An American study showed that 57.5% of analgesic opioid misuse occurred in methadone-maintained patients with chronic pain ( 21 ). Two recent studies also highlighted that the major source of diverted opioids was physician prescriptions ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first source is data from five studies within the Seek Test Treat and Retain (STTR) consortium funded by the National Institute of Drug Abuse(Chandler et al, 2015). The 5 studies included in these analyses were selected based on simultaneous collection of both adherence measures (described below) and were grouped into categories based on their study populations: criminal justice (CJ) (Carda-Auten et al, 2014; Gordon, Kinlock, McKenzie, Wilson, & Rich, 2013), international (Tomori et al, 2014; Wechsberg et al, 2014), or other vulnerable populations (VP) (Glenn et al, In press ). The second data source is the University of Washington site of the Centers for AIDS Research (CFAR) Network of Integrated Clinical Systems (CNICS)(Kitahata et al, 2008) cohort, a longitudinal observational study of PLWH in primary care.…”
Section: Methodsmentioning
confidence: 99%